1987
DOI: 10.1515/znc-1987-7-820
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Two Hydroxybiflavanonols from Garcinia cola Nuts

Abstract: The absolute configuration of two hydroxybiflavanonols from Garcinia cola nuts have been determined by CD and 500 MHz 1H NMR spectroscopy. Additionally the occurrence of atrop-isomers at room temperature as the consequence of rotational hindrance in the molecules could be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Isolation of the liver active constituents of G. kola seeds Garcinia biflavanonols, GB1 and GB2, were isolated from the seeds of G. kola as previously described (Sonnenbichler et al 1987). …”
Section: Experimental Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Isolation of the liver active constituents of G. kola seeds Garcinia biflavanonols, GB1 and GB2, were isolated from the seeds of G. kola as previously described (Sonnenbichler et al 1987). …”
Section: Experimental Animalsmentioning
confidence: 99%
“…Pharmacological studies on the biflavonoids from this seed plant showed that they have antihepatotoxic (Madubunyi 1983;Iwu 1985;Sonnenbichler et al 1987), anti-diabetic activity (Iwu et al 1990), antispasmodic effect on smooth muscle (Braide 1989), antithrombic effect (Olajide 1999), bronchodilatation in man (Orie and Ekon 1993), anti-inflammatory, and anti-viral properties (Adedeji et al 2006a). It is also active in the treatment of knee osteoarthritis (Adegbehingbe et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations